2008
DOI: 10.4103/0970-2113.44124
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of patients placed on treatment under directly observed therapy short-course (DOTS)

Abstract: Background:Tuberculosis continues to be a pressing health problem in India. The Revised National Tuberculosis Programme (RNTCP), an application of Directly Observed Treatment Short-course (DOTS) in India, launched in 1997 needs continuous evaluation.Objective:To study the outcomes of treatment among the patients put on DOTS under RNTCP in Chandigarh, UT.Material & Methods:A Longitudinal study was conducted during 2004-2005 in 13 Microscopic centres (MC's) spread over 2 Tuberculosis Units (TU's) under District … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
5
14
4
Order By: Relevance
“…6 Similarly, most patients in Category II treatment were also reported to be in the younger age group of 15 to 24 years in a study done in Chandigarh. 4 However the mean age of patients in Category I and II in the present study was higher than that of the Chandigarh study where it was 31.7±13.4 years for Category I patients and 32.3±14.0 years for Category II patients. 4 Another study done in West Bengal reported the mean age of Category II patients to be 41.8 years which was more than our findings.…”
Section: Discussioncontrasting
confidence: 78%
“…6 Similarly, most patients in Category II treatment were also reported to be in the younger age group of 15 to 24 years in a study done in Chandigarh. 4 However the mean age of patients in Category I and II in the present study was higher than that of the Chandigarh study where it was 31.7±13.4 years for Category I patients and 32.3±14.0 years for Category II patients. 4 Another study done in West Bengal reported the mean age of Category II patients to be 41.8 years which was more than our findings.…”
Section: Discussioncontrasting
confidence: 78%
“…High proportion of pulmonary tuberculosis cases on Cat-I similar to the present study from 81% to 95.5% were observed by A Mishra et al, 8 S L Chandha et al, 9 Abhijit M et al, 7 A L DaCosta et al 10 Almost similar sputum conversion rate by three months of Cat-I pulmonary tuberculosis cases was reported by Bawri S et al 11 (92%) and Gurpreet K et al 12 (93.8%). Simmi Tiwari et al 13 reported achievement below average (88.8%) and S Bisoi et al 6 also found poor conversion rate (74.2%) among new sputum positive cases.…”
Section: Treatment Activitiessupporting
confidence: 88%
“…In the present study, the cure rate among pulmonary tuberculosis cases was more (61%) when compared to a study conducted by Mahesh C et al 15 (43.3%) whereas studies conducted by A. Mishra et al 12 (85.04%) and S L Chadha et al 13 (90%) had high cure rates among pulmonary tuberculosis cases. The success rate seen in the present study (74.5%) was low as compared to the observation noted by R Prasad et al 16 of 89.4%, and default rate of 32.5% in a study by Mahesh C et al was very high compared to present study (4.5%), but findings of R Prasad et al 16 regarding default rate (3.79%) was low compared to the present study.…”
Section: Treatment Outcomescontrasting
confidence: 66%
“…In the present study, the default rate was 11.8% which is higher than 1.1% and 6.8% documented by Kaur et al (2008) [10] and Moharana et al (2009) [12] respectively. However, Sophia et al (2004) [8] and Jaggarajamma et al (2007) [9] observed a higher default rate of 24.7% and 20.0% respectively.…”
Section: Discussionmentioning
confidence: 47%
“…However, Kaur et al (2008) [10] reported that 36.9% subjects were illiterate, 15.9% were educated up to primary, 18.5% up to middle, 16.2% up to high school, 7.2% up to senior secondary and 4.2% were graduates, while Chadha and Bhagi (2000) [11] and Sophia et al (2004) [8] reported 39% and 29.2% illiterate subjects respectively.…”
Section: Discussionmentioning
confidence: 99%